The language of jokes in the digital age viral humour - Chiaro, Delia 1953- (Routledge, 2018)
"This book sets out to provide a fresh overview of the language of jokes and verbal humour in a globalized and digitalized world. Chiaro shows how, while on the one hand the lingua-cultural nuts and bolts of jokes have remained unchanged over time, on the other, the time-space compression brought about by new technology has generated new settings and new ways of joking and playing with language. Covering a wide range of settings from social networks, e-mails, videogames and RPGs (computer based Role Play Games) to more traditional fields of film and TV (especially sitcoms and game shows) and advertising, this lively book will be essential reading for any student or researcher working in the area of language and humour"--Provided by publisher.